Examining reading comprehension through the use of continuous texts and hypertexts - Coscarelli, Carla Viana (Colombian Applied Linguistics Journal, 2007)
In this paper we present the results of an experiment that aims to verify the influence of the presentation format – hypertext or continuous – in reading comprehension. A group of students, who are familiar with computers, read an advertisement in one of the formats: hypertext or continuous. After reading the text the students answered questions that aimed to verify some reading skills: global comprehension, retrieving information, making inferences and giving opinion. Both the text and the answers given by the students were analyzed using the Theory of Mental Spaces proposed by Fauconnier and Turner (2002). Although a quantitative analyses of the answers has pointed to an advantage of the hypertext format, qualitative analyses show that, regardless of the presentation format, the students could understand the advertisement, and were able to deal with different mental spaces in a very creative and efficient way.